Corporate Size and Rank Maintenance in the Malaysian Industrial Sector (Malaysian Management Journal, 1995)
The study empirically tests the hypothesis that firms try to maintain or improve their ranks. Malaysian data is used. The findings of the study indicate that; 1) companies, in general, try to maintain or improve their relative ranks in the corporate structure over time; 2) smaller and larger companies are more concerned about maintaining their ranks in the corporate hierarchy; 3) companies are more concerned with maintaining their ranks in the short run than in the long run; 4) the concentration of wealth and monopoly power of the largest eleven companies declined over the years as more companies were listed and mailer companies improved their positions in the industry; and 5) there is a non-significant relationship between asset-size and profitability of the firm, at least in the short run. However, the study indicates that in the long run, rank maintenance and profit maximization are complementary hypotheses.